A cor do trabalho informal: uma perspectiva de análise das atividades informais - Beloque, Leslie Denise (2007)
This study is about what was established to be called as informal work and whose objective is to assess the analytical perspective itself in which the informality is frequently studied, considering its difficulty to deal with the diversity of the informal activities. This assessment was seen through the contact, along seven years, with informal workers whose experiences and perceptions showed to be an analysis perspective of the extremely proficient informality . One of the main problems of the analysis of informality is the assumption that the informal workers and the small non-legally organized companies , which make part of the called informal sector , constitute an informal economical sector that operates as a cohesive block in the interstices of economy not taken by the big capital. However, as the bibliographic research advanced, was pointing out that, since the time the capitalist economy arose was constituted for the combination of capitalist ways of work with the other species of existing work. Therefore, the option of taking this fact as starting point of this analysis. Thus, the preparation of this study implied, initially, to assess the possibility that the main grounds of the modern science, that inspire the analytical perspective that conceives informality as an informal sector , are in the root of the inconsistencies of this analysis; then, the analysis of the experience of 20 informal workers, from both sexes and different ages, in order to identify the nature of their economic activities and how the informal work combines with the capitalist economy and, in the end, the proposition of an analysis perspective of the informal activities whose starting point is this combination. The main proposal of this study is that the capitalist economy is as the typically capitalists production ways, as the other existing kinds of work and that, in this interaction, they constitute mutually, that is, one brings life to the other and, in this movement, participate of the constitution process of the capitalist economy. Therefore, the informal activities do not constitute an informal sector that operates in the interstices of the economy, but are integral elements of the production or of the circulation sphere of economy, as well as of the core of the capital reproduction. Keywords: informal sector; analysis perspective of informal activities; perceptions about informal work